The Role of China in Contemporary International Law - Єделєв, Роман Сергійович; Співак, Владислав Михайлович (Київський національний університет імені Тараса Шевченка, 2024)
Abstract. In this article, China's practices in international trade, human rights, territorial disputes, and information technologies, are analyzed. The author emphasizes that China is ready to challenge international law when it conflicts with its interests. The article also highlights that China does not recognize the obligation to implement decisions of international courts and its national institutions refrain from engaging in human rights protection. The following methods were employed in the course of this research: systemic, comparative legal, historical and legal, structural and functional, and generalization. The author researches China's interest in the stability of rules of international law and its ability to interpret them freely, including in relation to the Russian-Ukrainian war. It was found that China is interested in applying existing international law rather than creating specific new norms, which aligns with its stance on sovereignty and non-interference. Special attention is paid to China's strategic approach to international law, balancing between adherence and reinterpretation to align with national interests.

Анотація. У цій статті аналізується міжнародно-правова практика Китаю в сферах міжнародної торгівлі, прав людини, територіальних суперечок та інформаційних технологій. Автор наголошує, що Китай готовий кинути виклик міжнародному праву, коли воно суперечить його інтересам. У статті також наголошується, що Китай не визнає зобов'язання виконувати рішення міжнародних судів, а його національні органи утримуються від захисту прав людини. У ході дослідження використовувалися такі методи: системний, порівняльно-правовий, історико-правовий, структурно-функціональний та узагальнення. Автор досліджує зацікавленість Китаю у сталості норм міжнародного права, як і у своїй можливості вільного їх тлумачення, у тому числі і стосовно російсько-української війни. Було виявлено, що Китай зацікавлений у застосуванні чинних норм міжнародного права, а не в створенні конкретних нових норм, що узгоджується з його позицією щодо суверенітету та принципу невтручання. Особливу увагу приділено стратегічному підходу Китаю до міжнародного права, що балансує між дотриманням і власним тлумаченням норм для узгодження з національними інтересами.
Роль Китаю в сучасному міжнародному праві
Keywords: internationallawChina; humanrightsChina; russianwarChina; міжнароднеправоКитай; правалюдиниКитай; російськавійнаКитай